2017
DOI: 10.1016/j.cedpsych.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous spatial strategy use in learning from scientific text

Abstract: Two studies explored the role of the spontaneous use of spatial note-taking strategies (i.e., creating maps and drawings) and spatial ability in learning from a scientific passage. In Study 1, college students read and took notes by hand on a 10-paragraph scientific passage about the human respiratory system. Students tended to use verbal strategies such as lists (on 48% of the paragraphs), outlines (29%) and running text (15%), but also used spatial strategies such as maps (28%) and drawings (11%). Regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 58 publications
(67 reference statements)
1
34
0
Order By: Relevance
“…An alternative, learner-managed solution is to ask students to generate their own images from the text (Ainsworth et al, 2011 ; Fiorella & Mayer, 2016 , 2017 ; Van Meter & Garner, 2005 ), as shown in Fig. 1c .…”
Section: Problem: Materials Contains Only Textmentioning
confidence: 99%
“…An alternative, learner-managed solution is to ask students to generate their own images from the text (Ainsworth et al, 2011 ; Fiorella & Mayer, 2016 , 2017 ; Van Meter & Garner, 2005 ), as shown in Fig. 1c .…”
Section: Problem: Materials Contains Only Textmentioning
confidence: 99%
“…According to the cognitive model of drawing construction (Van Meter & Firetto, 2013), creating drawings forces students to build connections among verbal and nonverbal representations by externalizing their mental model. Research suggests creating one's own pictorial representation of the learning material is generally more effective than using purely verbal strategies, such as writing summaries (Fiorella & Mayer, 2017; Fiorella & Zhang, 2018; Van Meter & Garner, 2005). For example, Leopold and Leutner (2012) found high school students who created drawing to represent a science text on water molecules exhibited deeper understanding than students who wrote verbal summaries.…”
Section: How Do Visuals Facilitate Explaining?mentioning
confidence: 99%
“…The first study to investigate this phenomenon found that students who were assigned to take notes by hand during a lab-based study showed greater learning than those assigned to take notes on a laptop [ 13 ]. In contrast, a different lab-based study found that laptop note-takers outperformed individuals who took notes by hand [ 23 ]. Finally, a third study found that the effects of various note taking media depend on whether students reviewed their notes [ 24 ].…”
Section: Introductionmentioning
confidence: 99%